Deep Wells and Prudence : Towards Pragmatic Action for Addressing Groundwater Overexploitation in India - World Bank (World Bank, 2012)
India is the largest groundwater user in the world, with an estimated usage of around 230 cubic kilometers per year, more than a quarter of the global total. With more than 60 percent of irrigated agriculture and 85 percent of drinking water supplies dependent on it, groundwater is a vital resource for rural areas in India. Reliance of urban and industrial waste supplies on groundwater is also becoming increasingly significant in India. Through the construction of millions of private wells, there has been a phenomenal growth in the exploitation of groundwater in the last five decades. The potential social and economic consequences of continued weak or nonexistent groundwater management are serious, as aquifer depletion is concentrated in many of the most populated and economically productive areas. The implications are disturbing for attainment of the millennium development goals, for sustaining economic growth and local livelihoods, and for environmental and fiscal sustainability. The consequences will be most severe for the poor. Furthermore, climate change will put additional stress on groundwater resources; while at the same time will have an unpredictable impact on groundwater recharge and availability.